Selection by Brent Geese Branta bernicla for different leaf lengths of Aster tripolium on saltmarsh - Summers, Ron W; Atkins, Clare (Wildfowl, 1991)
In early winter Brent Geese feeding on lower saltmarsh selected Aster tripolium leaves in the length classes 30-89 mm and especially 40-59 mm; i.e. in the mid-range of available sizes. Small leaves (mean size 25 mm) had proportionately more crude protein and water-soluble carbohydrates than large leaves (113 mm), and a lower ash, water and salt content. Thus, Brent Geese were not selecting the most nutritious leaves though they may have been selecting the mid-range to maximize the rate of intake of nutrients.